Received signal statistics in ds-cdma channels with flat rayleigh fading and fast closed-loop power control - Sim, Moh Lim; Chuah, Hean Teik (IEEE Xplore, 2003)
The statistics of received signal power at the receiver in a cellular direct-sequence code-division multiple-access (DS-CDMA) system with flat Rayleigh fading and fast closed-loop power control mechanism are studied. A simple model for fast closed-loop power control mechanism is proposed to ease the analysis. The probability density function (pdf) of the received signal power is derived by taking into consideration the updating frequency of power control mechanism, maximum allowable transmitted power, and Doppler frequency of the fading channel. The pdf derived can be used to study the performance of a reverse-link DS-CDMA system with noncoherent M-ary orthogonal modulation. The result shows that when optimum maximum allowable transmitted power is used, system capacity can be substantially increased for typical normalized Doppler frequency in cellular communication.